THE FORMATION OF SOPHISTIC VIEWS IN ANCIENT GREECE: STATE AND LAW ISSUES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article examines the spiritual, philosophical, and political movements of Ancient Greece. At the same time, the most characteristic features of Sophistics, moral standards, and the opinions expressed by the ancient Greek sophists about the issues of state and law in it have been deeply studied. The Sophists’ political views, important contributions to popularization of knowledge and culture are also studied.